IDEAL CONVERGENCE IN MODIFIED IFNS AND G-FUZZY NORMED SPACE - Khan, Vakeel A.; Et, Mikail; Khan, Izhar Ali (Amer Inst Mathematical Sciences-Aims, 2025)
This paper aims to present the concept of I & I* convergence and sp-I convergence along with the I Cauchy criterion in G-fuzzy normed space (in short G-FNS). Characterizations of these notions in G-FNS have been shown in the paper. This paper also presents how these notions are related to each other in G-FNS. We have also given certain important counter-examples to establish the relationships between them. In addition, we introduce the G-fuzzy limit points and G-fuzzy cluster points of a sequence in G-FNS.
Keywords: Ideal convergence; sp-convergence; G-fuzzy normed space